New records of Scomberoides tala (Cuvier, 1832), Barred Queenfish (Actinopterygii, Carangiformes, Carangidae), from southwestern Taiwan - Yo Su; Yu-Chieh Hsu; Tzu-Yung Lin (Check List)
Specimens of Scomberoides tala (Cuvier, 1832) were collected from southwestern Taiwan in the northwestern Pacific Ocean. While this species has been documented in other regions of the northwestern Pacific, our specimens mark its first recorded occurrence in Taiwan, bridging a previously identified distribution gap in this region. Additionally, we suggest that the distribution of this species may be shifting northward, potentially driven by global warming, as the northern records were reported rather recently.